1989
DOI: 10.1093/jmedent/26.3.228
|View full text |Cite
|
Sign up to set email alerts
|

Urogenital Myiasis Caused by Megaselia scalaris (Diptera: Phoridae): A Case Report

Abstract: A case of urogenital myiasis in a patient with transverse myelitis is reported from Imphal, Manipur, India. The larvae of Megaselia scalaris Lowe were recovered repeatedly from the urine of the patient and were reared to adult to facilitate identification. This is the first known case of urinary myiasis caused by M. scalaris in India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…Identification of the species of maggots prior to treatment is important since not all types of myiasis are benign (Singh and Rana, 1989). The present work focused on an ordinary microscopy for identification of the larvae.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of the species of maggots prior to treatment is important since not all types of myiasis are benign (Singh and Rana, 1989). The present work focused on an ordinary microscopy for identification of the larvae.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to causing myiasis in humans (Trape et al 1982, Singh et al 1988, Singh & Rana 1989, it has also been reported as a forensically-important fly (e.g. Barnes 1990, Disney 1994.…”
mentioning
confidence: 99%
“…Several workers reported cases of intestinal myiasis due to M. scalaris [7][8][9]. Hira et al [10] described in 2004 a case of nosocomial myiasis in Kuwait caused by M. scalaris.…”
Section: Discussionmentioning
confidence: 99%
“…Hira et al [10] described in 2004 a case of nosocomial myiasis in Kuwait caused by M. scalaris. The first report of human urogenital myiasis due to a species of Megaselia was represented in 1978 by Disney and Kurahashi [11], and then more cases were reported [12][13][14]. Other workers studied invasion of ticks [15], bananas [16], and snacks [17] by the larvae of M. scalaris.…”
Section: Discussionmentioning
confidence: 99%